1975
DOI: 10.1042/bj1510399
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of kynurenine-2-oxoglutarate aminotransferase from the liver, brain and small intestine of rats

Abstract: 1. Kynurenine-2-oxoglutarate aminotransferase (isoenzyme 1) was purified to homogeneity from the liver, brain and small intestine of rats by the same procedure. The three enzyme preparations had nearly identical pH optima, substrate specificities and molecular weights. Isoenzyme 1 was active with 2-oxoglutarate but not with pyruvate as amino acceptor, and utilized a wide range of amino acids as amino donors. Amino acids were effective in the following order to activity: L-aspartate greater than L-tyrosine grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

1976
1976
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 23 publications
(19 reference statements)
0
20
2
Order By: Relevance
“…Recent reports have shown that several enzymes catalyze the transamination of L-KYN and various 2-oxo-Baran/Staniek/Kepplinger/Gille/Stolze/ Nohl acids to KYNA in various tissues [18][19][20] and the CNS [18][19][20][21][22]. The enzymes kynurenine aminotransferases (KATs) have been identified and characterized in several organs [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that several enzymes catalyze the transamination of L-KYN and various 2-oxo-Baran/Staniek/Kepplinger/Gille/Stolze/ Nohl acids to KYNA in various tissues [18][19][20] and the CNS [18][19][20][21][22]. The enzymes kynurenine aminotransferases (KATs) have been identified and characterized in several organs [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes kynurenine aminotransferases (KATs) have been identified and characterized in several organs [18][19][20][21][22]. It is known that some of the transaminases are localized in the inner membrane of mitochondria [16].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the transamination of the three amino acids is catalysed by a single enzyme. Recently, we reported that isoenzyme 1 is identical with the mitochondrial aspartate 2-oxoglutarate aminotransferase, and also with the mitochondrial tyrosine 2-oxoglutarate aminotransferase, suggesting that the transamination of kynurenine by this enzyme does not function in the physiological condition [27,28] i<h e apparent^ values of the purified isoenzyme 3 for kynurenine was lower than thosel 29 ' 30 ! of isoenzymes 1 and 2.…”
Section: Discussionmentioning
confidence: 88%
“…The occurrence of KYNA has been confirmed practically in all brain cells, in the digestive system, peripheral blood, saliva and in organs such as the heart and liver, but the level of this acid in healthy individuals is relatively low (Noguchi et al . ; Turski et al . ; Baran et al .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the endogenous level of KYNA in the brain may change in pathologic conditions as Alzheimer's disease, schizophrenia or Parkinson's disease (Ogawa et al 1992; Baran, Jellinger & Deecke 1999;Erhardt et al 2001). The occurrence of KYNA has been confirmed practically in all brain cells, in the digestive system, peripheral blood, saliva and in organs such as the heart and liver, but the level of this acid in healthy individuals is relatively low (Noguchi et al 1975;Turski et al 1988; Baran et al 1997;Amirkhani et al 2002). Its concentration, however, rises to the micromolar level in inflammatory conditions or infections.…”
Section: Introductionmentioning
confidence: 99%